Reflections on an Anglophone academic sect - Hann, Chris (The Australian journal of anthropology, 2017)
While saluting the ethnographic originality of the contents of this special issue and the ambition of its editors to extend recent debates in the anthropology of Christianity to large Catholic populations in Asia, the author argues that the contributors remain in thrall to Protestant tenets of rupture and individualism. He urges more balanced coverage of the diversity of Christian communities and more attention to a long history of anthropological engagement with them.